Beyond the Institution: Transforming the Learning Environment in Architectural Education - der Technischen Universität Graz, Architekturfakultät (GAM - Graz Architecture Magazine, 2022)
New and cutting-edge forms of pedagogy such as distance learning, design-build, collaborative learning, and peer-to-peer practices are increasingly calling conventional teaching and learning environments, in architecture and other design disciplines, into question. Academic institutions in Western Europe, in particular, are faced with the challenge of rethinking standardized spatial structures and institutional hierarchies and adapting them to unconventional and radical teaching and learning concepts. GAM.18 explores anew the area of conflict between architecture teaching in universities and the teaching environment. It calls for spatial structures and working environments that enable the contemplation and design of architecture, and investigates teaching and learning methods that include critical consideration of the spaces and institutions in which the teaching takes place. With contributions from Hélène Frichot, Charlotte Malterre-Barthes, Lucia Pennati, Jean-Louis Violeau, and others.